Ergonomic Analysis Of Educational Situations In The Algerian School - Benayache, Houria; Belhay, Hacina; Boussaha, Abla (جامعة الوادي - University of Eloued, 2023)
Educational institutions are a fertile field for ergonomic applications through what the ergonomics offers in terms of solutions, not only, for wrong positions and designs, but also by studying the cognitive processes of the individual at work related to information capture ,processing and storage.Also this includes studying all technical arrangements that lead to adapt and organize the work environment. Through this article, we discuss the importance of educational ergonomics in improving learning conditions, adapting the school environment and making it healthy and safe for both the student and the teacher. This comes with a focus on the ergonomic analysis of the reality of educational situations in Algerian school, which in their entirety are difficult situations, not adapted and donot provide a healthy work environment. Additionally, the article talks about the most important difficulties that prevent the real application of ergonomics in the Algerian school. الملخص : تعتبر المؤسسات التربوية مجالا خصبا للتطبيقات الأرغونومية من خلال ما تقدمه الأرغونوميا من حلول،ليس فقط للوضعيات والتصاميم الخاطئة و إنما كذلك من خلال دراسة العمليات المعرفية للفرد في العمل والتي تتعلق بالتقاط المعلومات و معالجتها وتخزينها، و دراسة كل الترتيبات الفنية التي تؤدي إلى تكييف بيئة العمل و تنظيمه . من خلال هذا المقال نتطرق إلى أهمية الأرغونوميا التربوية في تحسين الوضعيات التعليمية وتكييف المحيط المدرسي و جعله آمنا و مريحا لكل من التلميذ والمعلم.هذا مع التركيز على التحليل الأرغونومي لواقع الوضعيات التربوية و التي تعتبر في مجملها وضعيات صعبة ، غير مكيفة و لا توفر بيئة مدرسية سليمة .إضافة إلى الحديث عن أهم الصعوبات التي تحول دون التطبيق الفعلي للأرغونوميا التربوية في المدرسة الجزائرية.
مقال
Keywords: Educational Ergonomics, Ergonomic Analysis, Educational Situations; األرغونوميا التربوية، التحليل األرغونومي، الوضعيات التربوية